PENGARUH CEKAMAN KEKERINGAN TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS KEDELAI (GLYCINE MAX L. MERRILL) - Nurjanah, Titik; Julianto, Reza Prakoso Dwi; Hamzah, Amir (Fakultas Pertanian, 2019)
Soybean is one of the multipurpose plants because it can be used as food, feed, or raw materials processing industry. One of the arguments in the field is the investment problem that does not get maximum results. The method used in this study is the random group factorial design (RAKF) There are 12 repeated treatments 3 times, resulting in 36 units of trial. Each unit of trial consists of 3 polybags containing plants, where each unit of trial is taken 3 samples of plants. Each unit of experiment consisted of 3 polybags, where each unit of experiment was taken 3 plant samples. The first factor is three soybean varieties, among others: V1 (Agromulyo), V2 (Grobogan), V3 (Anjasmoro) and the second factor is the level of the Cekaman, among others: 1/4 KL, 2/4 KL, 3/4 KL, 4/4 KL). The capacity of the land is determined by the soil way of 10 kg collected in composite which has been selected and the ground is first dried. Land as much as 10 kg that has been obtained into a black polybag diameter 50 cm and then watered water until the first water droplets, pouring water until the first drop is 1.5 L as a space capacity. The observation parameters performed include: Height of the plant (cm), number of leaves (strands), the weight of fresh seed cropping (g), the weight of the dried seed cropping (g), the number of cropping beans and the leaf color. The results of the study can be concluded the interaction of the degree of treatment of some of the best soy varieties is found IN V3TCC (Anjasmoro varieties with a level of 1,125 ml). Keywords : the dryness of drought, soy. Kedelai merupakan salah satu tanaman multiguna karena bisa digunakan sebagai pangan, pakan, maupun bahan baku industri pengolahan. Salah satu kendala dilapangan adalah masalah kedelai yang diteliti tidak mendapatkan hasil yang maksimal. Metode yang digunakan dalam penelitian ini adalah Rancangan Acak Kelompok Faktorial (RAKF) Terdapat 12 perlakuan yang diulang 3 kali, sehingga 36 unit percobaan. Setiap unit percobaan terdiri dari 3 polybag, dimana setiap unit percobaan diambil 3 sampel tanaman. Faktor pertama yaitu tiga varietas kedelai antara lain: V1 (Agromulyo), V2 (Grobogan), V3 (Anjasmoro) dan faktor kedua adalah tingkat cekaman antara lain: ¼ KL, 2/4 KL, ¾ KL, 4/4 KL). Kapasitas lapang ditentukan dengan cara tanah 10 kg dikumpulkan secara komposit dilahan yang telah terpilih dan tanah terlebih dahulu dikeringkan. Tanah sebanyak 10 kg yang telah didapatkan dimasukkan kedalam polybag hitam berdiameter 50 cm kemudian disiram air sampai keluar tetesan air pertama, penuangan air sampai tetes pertama adalah 1,5 l sebagai kapasitas lapang. Parameter pengamatan yang dilakukan meliputi : Tinggi tanaman (cm), jumlah daun (helai), bobot biji segar pertanaman (g), bobot biji kering pertanaman (g), jumlah biji pertanaman dan warna daun. Hasil penelitian dapat disimpulkan bahwa Interaksi pemberian tingkat cekaman terhadap beberapa varietas kedelai perlakuan terbaik terdapat pada V3TCC (Varietas Anjasmoro dengan tingkat cekaman 1.125 ml).